+0  
 
0
91
1
avatar+2765 

Suppose that \(f\) is a function and \(f^{-1}\) is the inverse of \(f\). If \(f(1)=2\)\(f(2) = 6\), and \(f(3)=5\), then what is \(f^{-1}(f^{-1}(6))\)?

tertre  Mar 11, 2018
 #1
avatar+87333 
+1

f(1)  = 2  ⇒  f-1(2)  = 1  

 

f(2)  =  6     ⇒  f-1(6)  = 2

 

So

 

f-1 (f-1 (6) )   =   f-1 (2)  =   1

 

 

cool cool cool

CPhill  Mar 11, 2018

11 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.